Peranan Pengabdian pada Masyarakat UNRI sebagai wujud pengabdian Kepada Masyarakat Desa Berancah di Tengah Pandemi Covid-19 - Aldi Maat Syhafutra; Muhammad Faizal Noor; M. Ikhsan Fahrorrozi; Dr. Auradian Marta, S.IP., MA; Novi Nanda Yusri; Dessy Wulandari; Nurul Huda Aulia; Adhe fadhila; Novianti Dita Sari; Chintya Gusti Yulanda; Sri Wulan Fajriani (LP2M Universitas Muhammadiyah Enrekang, 2022)
Community service Balek Kampung during the covid-19 pandemic are different from community service in general. Community service balek kampung during the covid-19 pandemic can be done in groups boldly and semi-daing (directly in the field on a limited basis). With the existence of Community service in the midst of the covid-19 pandemic, it is hoped that students will still have the urgency of service so that they can develop student competencies and social interactions in the community. This study aims to determine the role of Real Work Lectures as a form of community service. Methods of data collection using the method of observation and documentation. Observation is an observation in the form of a series of activities to focus on an object with the senses. The documentation method used in this study is to support data such as data on Community service participants, community service locations, and community service activities. The results of this study indicate that community service activities as a form of community service during the pandemic can still be enjoyed by the community and the role of students can still be carried out with a series of innovative activities and continue to carry out health protocols